Analisis Perencanaan Pembangunan Dan Pertumbuhan Ekonomi Hijau di Indonesia - Irsyad Muhammad; Suharno Suharno; Barokatuminalloh Barokatuminalloh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study is to analyze Development Planning and Green Economic Growth in Indonesia. Environmental damage and low public awareness of the environment encourage the need for sustainable development. Environmental damage occurs due to high exploitation of natural resources to meet economic interests without being followed by awareness to protect the environment. This research method uses a quantitative research design, considering that the variables studied are in the form of numbers that are processed using statistical methods. Testing of this variable uses the Panel Least Squares method data processing, the results of which will be interpreted to see the effect of the tested variables on the dependent variable. This test uses the variables of carbon emission growth, economic growth, population growth, and human development index on the Environmental Quality Index. The results of the study indicate that carbon emission growth and economic growth have a significant negative effect on the environmental quality index. Population does not affect the environmental quality index, while the Human Development Index has a significant positive effect on the environmental quality index. The implication of this study is that the government needs to maintain economic growth by paying attention to environmental conditions and minimizing carbon emissions so that environmental quality can be maintained. The quality of human capital also needs to be continuously improved so that public awareness of the importance of environmental quality.